The false friend - Goldberg, Myla. (New York : Doubleday, 2010)
Celia and Djuna ruled their clique of friends with dual iron fists. But when Djuna disappeared while the duo was walking home together, Celia buried the terrible truth of that day deep down inside. Now, twenty years later, Celia is unable to consciously keep her secret any longer. Despite her success, her personal life has fallen stagnant, and, buried under the weight of her awful past, Celia returns to her hometown to confess her sins.
edited hb 2015-06-16
Keywords: Schoolgirls -- Fiction; Female friendship -- Fiction; Deception -- Fiction; Memory -- Fiction; Children -- Death -- Fiction; New York (State) -- Fiction; Psychological fiction